Improving The Performance of Omah Oveje MSME in Banyuanyar Village, Ampel, Boyolali Regency - Stacia Reviany Mege; Anafil Windriya; Sri Utami Handayani (GOTAVA, 2025)
This Community Service Program (PKM) aims to improve the performance of UMKM Omah Varian Jahe in Dukuh Jumbleng, Desa Banyuanyar, Boyolali, by addressing production and marketing challenges. The identified issues include poor product quality (taste, color, and cleanliness) due to manual ginger cleaning, low product demand, and insufficient sales performance, with sales only reaching 60-70 units per month and low pricing. Other problems include inadequate packaging (clear standing pouch) and unattractive labels, limited marketing strategies, and a lack of understanding in price calculation. In response, the PKM team provided training on production cost calculations, product photography, social media management, and selling via online marketplaces. Additionally, a ginger washing and peeling machine was provided. As a result, the team successfully facilitated the procurement of packaging materials (plastic jars, bottles, and stickers), created a new Instagram account for marketing, and improved production cost calculation knowledge by more than 85%. Furthermore, 500 custom standing pouches were provided for the instant ginger powder product, which is currently in production. These initiatives are expected to enhance product quality, marketing, and sales performance, helping UMKM Omah Varian Jahe grow